2018
DOI: 10.21037/atm.2018.03.23
|View full text |Cite
|
Sign up to set email alerts
|

Prepsoas oblique lateral lumbar interbody fusion in deformity surgery

Abstract: Interbody fusions are routinely used in deformity surgery to achieve both coronal and sagittal correction and attain increased fusion rates. Minimally invasive interbody techniques, including the prepsoas approach, are being utilized to decrease tissue disruption, blood loss, and patient morbidity with similar outcomes compared to traditional surgery. The prepsoas oblique lateral interbody fusion, accesses the spine between the iliac arteries or aorta and psoas muscle, and allows for exposure of the lumbar spi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Transient thigh symptoms are always experienced postoperatively and could be as high as 62.7% in XLIF cohorts (19). For OLIF, prior studies reported rates ranging from 1.3% to 21.4% (1,13,17), but these are likely underestimated because only motor dysfunction was described and not sensory abnormalities. Adverse postoperative neurological effects are still a significant concern despite intraoperative nerve monitoring (20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transient thigh symptoms are always experienced postoperatively and could be as high as 62.7% in XLIF cohorts (19). For OLIF, prior studies reported rates ranging from 1.3% to 21.4% (1,13,17), but these are likely underestimated because only motor dysfunction was described and not sensory abnormalities. Adverse postoperative neurological effects are still a significant concern despite intraoperative nerve monitoring (20).…”
Section: Discussionmentioning
confidence: 99%
“…Lumbar interbody arthrodesis is a safe, effective surgical procedure to treat lumbar disc herniation, degenerative disc disease, instability in lumbar spondylolisthesis, spinal deformity, and discogenic back pain. It can increase fusion rates and correct coronal and sagittal alignment (1).…”
Section: Introductionmentioning
confidence: 99%
“…The overall incidence of complications is reported to be 11.2-48.3%, including fatal abdominal aorta/iliac artery injury, segmental artery injury, peritoneal injury, lumbar myasthenia, ureteral injury, spinal nerve injury, sympathetic nerve injury, incision pain, cage subsidence (CS)/retropulsion, infection, retrograde ejaculation, etc. [5][6][7][8] . Among these complications, CS is considered to be signi cantly related to worse clinical outcomes [9] .…”
Section: Introductionmentioning
confidence: 99%
“…Early data showed that bleeding, surgical time, and postoperative recovery had favorable results. 3 Historically, lateral lumbar interbody fusion (LLIF) has been done with a true lateral view under fluoroscopy, but the OLIF is done from an oblique trajectory. 4,5 This oblique angle can be somewhat disorienting for surgeons, and navigation may be one method to help abate this disorientation.…”
Section: Introductionmentioning
confidence: 99%